Judicial Activism Approach of Religious Court Judges in the Perspective of Maqashid al-Shariah - Muh. Syahril Sabirin; Kurniati Kurniati; Zulhas’ari Mustafa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the application of judicial activism by Religious Court judges from the perspective of maqashid al-shariah and its implications for the realization of substantive justice. This research employs a normative legal method with a library research approach. The data were collected from primary, secondary, and tertiary legal materials, including legislation, court decisions, jurisprudence, books, and relevant scholarly journals. Data were analyzed using a descriptive-qualitative method. The findings indicate that judicial activism provides judges with the opportunity not only to apply written legal norms but also to actively explore and uphold the values of justice that exist within society. This approach is highly relevant to maqashid al-shariah because both are oriented toward promoting public welfare (maslahah), protecting rights, and preventing harm. The implementation of judicial activism is reflected in judicial decisions where judges exercise ex officio authority to protect the rights of vulnerable parties, even when such claims are not explicitly requested in the petition. Consequently, judges are able to realize substantive justice that is more responsive, humane, and oriented toward safeguarding the rights of litigants in accordance with the objectives of Islamic law and the evolving needs of society.